Personality as predictor of psychological well-being among older adults - Brković, Irma (Array, 2010)
The aim of the research was to explore the relations between personality traits and indicators of psychological well-being among older adults. Participants were 134 retirees (76, 1% female), 68 (50, 7%) of whom lived in retirement home, and others living at home. Five Factor Personality Inventory (FFPI, Hendriks, Hofstee & De Raad, 1999) was used to measure personality traits – Extraversion, Agreeableness, Conscientiousness, Emotional stability and Autonomy. We measured three aspects of psychological well-being: Self-Esteem (Rosenberg, 1965), Loneliness (UCLA-3 short version, Russell & Cutrona, 1988) and Life-satisfaction (Index of General Affect and Index of Well-Being, Campbell et al., 1976). Separate preliminary analyses have shown that, as expected, Extraversion and Emotional Stability, as well as education, were consistent predictors of all four aspects of Psychological well-being, with only Conscientiousness being additional predictor of Self-Esteem. Factor anal ysis of psychological well-being measures revealed that single indicator of Psychological well-being can be formed. First component explained 56, 8% of variance of four well-being measures. Hierarchical regression analysis was conducted, with demographic variables (gender and age) added in step1, five personality traits in step 2 and education in step 3. While gender and age were not significantly related to well-being, personality traits were significant predictors of well-being with Extraversion and Emotional stability positively related to the outcome. Education, added in the last step, significantly improved outcome prediction, above personality traits. Higher education was positively related to psychological well-being.